Effectiveness of The Constructionist Approach on Economics Learning Achievement in Material Model Diagram Interaction of Economic Actors Class I - Ahmad Salami (Berpusi Publishing, 2024)
Objective study This is 1) for know Performance Study student with Which No using a constructivism approach, 2) to determine students' learning achievements using PBL Model learning, 3) to find out what exists difference on performance Study between Which No use approach constructivism by using a constructivist approach to student economics material class I This research is a quantitative research with a post test only control design design. The place used for this research was SMP N 3 Muarasipongi One Roof . The research population was 15 students from class IX, using simple random sampling techniques. Data collection technique with written tests and documentation. Class I X as an experimental class. Technique analysis data Which used For analyze data in This research is an analysis t-test statistical data. Based on test score results. Student showing post-test average score the experimental class was 80.8 and the average post-test score for the control class was 67.6. For experimental class which means good, based on the analysis results it is known that the significance level is 5% for mark 68 (significant level of 5% or 1% for N = 70 and dk = 68, because dk = 68 does not listed in table distribution t so taken mark 60) Mark t table of et al = 60 is 2.02 And 5.756 which means t count > t table, Ho is rejected and Ha is accepted. So